Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1597/12-214
|View full text |Cite
|
Sign up to set email alerts
|

Airway Management in Pierre Robin Sequence: Patterns of Practice

Abstract: Objectives : To report survey results from American Cleft Palate-Craniofacial Association members on the practice patterns of airway obstruction management in patients with Pierre Robin sequence. Design : A 10-question online survey was sent and the data were reviewed. Setting : Online survey of members of the American Cleft Palate-Craniofacial Association. Patients : Surveys assessed management patterns of patients with Pierre Robin sequence whom a surgeon member of the American Cleft Palate-Craniofacial Asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 30 publications
0
30
0
1
Order By: Relevance
“…We regard CPAP There is heterogeneity of approach to management of UAO in RS, with no evidence-based clinical practice guidelines to direct management. 23 This lack of uniformity in approach was highlighted by a recent survey of practices across 101 European centers, which showed that NPA, CPAP, and palatal plates were strongly favored in the UK, France, and Germany, respectively. 7 Only 7% of our cohort required surgical airway management which concurs with the findings of recent large studies.…”
Section: Discussionmentioning
confidence: 99%
“…We regard CPAP There is heterogeneity of approach to management of UAO in RS, with no evidence-based clinical practice guidelines to direct management. 23 This lack of uniformity in approach was highlighted by a recent survey of practices across 101 European centers, which showed that NPA, CPAP, and palatal plates were strongly favored in the UK, France, and Germany, respectively. 7 Only 7% of our cohort required surgical airway management which concurs with the findings of recent large studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent online survey of American Cleft Palate–Craniofacial Association members on the practice patterns of management of upper airway obstruction in patients with PRS revealed a wide variation in personal practice (93). Mandibular distraction was the most common primary procedure, followed by tongue-lip adhesion, and then tracheostomy.…”
Section: Treatment Of Osa In Children With Pierre Robin Sequencementioning
confidence: 99%
“…There are various treatments available (positioning, nasopharyngeal airway, tongue‐lip‐adhesion, mandibular distraction, and tracheotomy [Evans et al, ]. The choice between treatment schedules depends on the severity of the problems, but decision making is often based on the physician's preference, training habits, and subspecialty category [Collins et al, ; Basart et al, ]. At present, it remains uncertain which treatment is best.…”
Section: Introductionmentioning
confidence: 99%